Bird Diversity and Community Composition in Kafta Sheraro National Park, Tigray, Northern Ethiopia - Girmay, Teklay; Teshome, Zeyede; Tesfamichael, Tesfay (International Journal of Zoology, 2020)
Birds are one of the most important components of biodiversity that has huge ecological, economical, and esthetic values. The main objective of this study was to assess diversity and species composition of bird community in Kafta Sheraro National Park, Northern Ethiopia. Data were collected from August 2017 to March 2018 in the national park. Point count method was employed to collect data on bird species diversity and species composition. Direct observations of birds and discussion with local people and scouts to assess potential threats of avifauna in the park were made. Shannon diversity index was used to calculate the species diversity. A total of 158 bird species belonging to 52 different families and 20 orders were identified. Of the recorded species, there were 76.6% residents, 15.8% Palaearctic migrants (PM), 5.7% Intra-African migrants (IM), and 1.9% partial migrants. Accipitiridae (11.4%) had the highest species followed by Columbidae, Estrilidae, and Ploceidae with 7%, 5.7%, and 4.4% species, respectively. The highest Shannon–Weiner diversity index (H′ = 4.50) was recorded during February while the lowest (H′ = 2.18) was recorded during March. Species richness of the park showed no significance difference among the study months (χ2 = 10.046, df = 5, P>0.05). Agricultural expansions, fire, livestock grazing, mining, and poaching were the major threats of the park bird species. Kafta Sheraro National Park is one of the areas with high avian composition in Ethiopia. In the park, wildlife watching in general and ornithological tourism in particular should be developed. Anthropogenic disturbances should also be minimized to conserve avian diversity of the park.